I am brazilian, you are paraguayan: national and local identity of students on the Brazil-Paraguay border (Research, Society and Development, 2022)
We start from an expanded location of, since the question of your question, in its symbolic meanings of the border and imaginary, presents results much more complex than normally noticed through the demarcation lines, of stories in progress as. This article aims to present how elementary school students perceive the relationship between local (border) and national (Brazilian or Paraguayan) identity. A descriptive-type qualitative-research was carried out, an instrument for data production, a main instrument (semi-structured) applied to elementary school II in a state city of Ponta Porã, which shares a dry border with Pedro Juan Caballero (Paraguay). On the frontier, hybrids form several mutable identities. The Brazilian evaluations of the data indicate that the frontier being presents itself as a striking identity in the lives of these students, who have their hybrid identity, especially regarding their hybrid and/or Paraguayan identity.